THE FAILURE OF TRANSITIONAL JUSTICE IN AFGHANISTAN: THE POLITICAL DIMENSION - Badloon, Bilal (American International Journal of Social Science Research, 2021)
In every phase of the conflict in Afghanistan, serious War Crimes and crimes against humanity were committed, resulting in mass killings and forced displacement of millions of Afghan civilians and political opponents. Based on relevant literature, this article investigates the political factors responsible for the failure of transitional justice in Afghanistan, particularly internal and external factors. The article also brings to the fore the impact of the dual process of state-building and peace-building on the implementation of transitional justice. In addition, the paper investigates why the ’Peace first and justice later’ strategy proved to be unsuccessful in Afghanistan as the Taliban continued their atrocities, fighting Afghan forces and killing innocent people in suicide attacks. The paper finds that the failure of transitional justice in Afghanistan is due to both internal and external factors. Further, the paper finds that Afghanistan has never been a post-conflict state, unlike other countries that have experienced transitional justice processes. Therefore transitional justice measures were never implemented. JEL Classification Codes: F51, F5.